2005
DOI: 10.1037/1053-0797.15.4.271
|View full text |Cite
|
Sign up to set email alerts
|

A method for recognizing and describing the links among dream sources.

Abstract: A method is described for the identification of possible links among dream sources and the study of their possible significance. The analysis is based on the automatic recognition of word root recurrences in text files, including dream reports and associations. Two tools are then applied: graph representation and grammar analysis. Graph representation of the detected links provides a quantitative description of some of their basic features. Grammar changes for recurrent word roots can imply remarkable context … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Furthermore, when applying the model to a dream and interpretation via The Storytelling Method, the explanatory power of the model becomes apparent. The psychophysiological model builds on previous research (Barcaro, et al, 2005) and adds a new model which appears to be thorough and all-encompassing in terms of the complex process of dream production and dream interpretation. Further inquiry and applications of the model for The Storytelling Method is certainly warranted for future research especially with EEG measures with both dream content and dream interpretaion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, when applying the model to a dream and interpretation via The Storytelling Method, the explanatory power of the model becomes apparent. The psychophysiological model builds on previous research (Barcaro, et al, 2005) and adds a new model which appears to be thorough and all-encompassing in terms of the complex process of dream production and dream interpretation. Further inquiry and applications of the model for The Storytelling Method is certainly warranted for future research especially with EEG measures with both dream content and dream interpretaion.…”
Section: Discussionmentioning
confidence: 99%
“…Hartmann, 1995), a basic property of the dream builder system is that of making connections. The dream sources are closely interwoven, and graphs representing the sources as nodes and the arcs as links can be semantically interpreted according to heuristic rules (Barcaro, Cavallero, Navona, 2005). From this point of view, the dream builder system can be described as a feedback system (Barcaro, 2010), because the output (i.e.…”
Section: I J O Rmentioning
confidence: 99%
See 1 more Smart Citation
“…Patterns of connections among different memory sources have been described (Barcaro et al, 2005 ; Barcaro, 2010 ): these connections, which can be identified by textual analysis of associations with the dream, often regard distant episodes of the dreamer’s life and often surprise the dreamer himself or herself. These patterns establish unexpected, often enlightening, correspondences between the different sources.…”
Section: Basic Features Of Dreaming That Can Give Effective Tools Formentioning
confidence: 99%
“…Furthermore, the occurrence of the phenomenon that Freud called "condensation" (i.e., reference of a single item of the dream experience to more than one waking experience) is very frequent in dreams, thus witnessing the existence of complex connections: for this reason, condensation should be credited with a phenomenological value, independently of the validity level of the Freudian theory. For each of the dreams examined, we identified link patterns between different dream sources according to the following criterion (Barcaro, Cavallero, & Navona, 2005): possible links exist when the associations relating to different sources contain words that either have the same stem or are semantically very close. Then we checked whether it was possible (Barcaro et al, 2005;Barcaro & Rizzi, 2010):…”
mentioning
confidence: 99%